1993
DOI: 10.1111/j.1476-5381.1993.tb13950.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the adenosine receptor mediating contraction in rat colonic muscularis mucosae

Abstract: 1 The objective of this study was to characterize the adenosine receptor mediating contraction in rat isolated colonic muscularis mucosae (RCMM). 2 Sequential additions of the adenosine receptor agonist 5'-N-ethylcarboxamidoadenosine (NECA; 0.01 -10 gM) elicited reproducible, concentration-related contractions in RCMM. The effects of NECA were mimicked by the adenosine Al receptor-selective agonists cyclopentyladenosine (CPA), Rphenylisopropyladenosine (R-PIA) and N-[1S, trans)2-hydroxycyclopentyl] adenosine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…However, immunohistochemical expression of P2X1 receptors in the smooth muscle of the muscularis mucosae, but not the muscularis externa, suggested that P2X1 rather than P2Y receptors were involved. The presence of P1 (A 1 ) receptors in rat colon muscularis mucosae, mediating contraction, was confirmed in a later study [566], although part of the response was claimed to be due to products of the cyclooxygenase pathway [567]. ATP inhibited swelling-activated Cl − currents in canine colonic smooth muscle, and it was suggested that this may be related to the regulation of myogenic activation in response to distension [181].…”
Section: Receptor Identificationmentioning
confidence: 90%
“…However, immunohistochemical expression of P2X1 receptors in the smooth muscle of the muscularis mucosae, but not the muscularis externa, suggested that P2X1 rather than P2Y receptors were involved. The presence of P1 (A 1 ) receptors in rat colon muscularis mucosae, mediating contraction, was confirmed in a later study [566], although part of the response was claimed to be due to products of the cyclooxygenase pathway [567]. ATP inhibited swelling-activated Cl − currents in canine colonic smooth muscle, and it was suggested that this may be related to the regulation of myogenic activation in response to distension [181].…”
Section: Receptor Identificationmentioning
confidence: 90%
“…Contractions were produced by the non-selective adenosine receptor agonist, 5'-N-ethylcarboxamidoadenosine (NECA); the adenosine Al-selective agonists, cyclopentyladenosine (CPA), R-phenylisopropyladenosine (R-PIA) and N[(lS,trans)-2-hydroxycyclopentyl]adenosine (GR79236) and by the A2-selective agonists, metrifudil and 2-[p- (2-carboxyethyl) phenylethyl amine)-5'-N-ethylcarboxamidoadenosine (CGS21680). The rank order of agonist potency (CPA > GR79236 = R-PIA > NECA>metrifudil>CGS21680; Reeves et al, 1993b) was identical to that obtained for the ' Author for correspondence. inhibition of spontaneous rate in rat isolated right atria and the inhibition of lipolysis in rat isolated adipocytes, two adenosine A1 receptor containing preparations (Gurden et al, 1993).…”
Section: Introductionmentioning
confidence: 55%
“…We also found that the non-selective adenosine A,/A2 receptor antagonist, 8-phenyltheophylline (8-PT;Collis et al, 1985), not only antagonized concentration-effect curves to NECA but also augmented its maximum response (Reeves et al, 1993b). The purpose of the present study therefore was to investigate further the characteristics of this augmentation by the use of a number of different adenosine receptor agonists and antagonists.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations